Insulating resin with improved ductility and laminate film prepared therewith

CN122935574APending Publication Date: 2026-10-16HANWHA YISHENSHA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202680000538.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-02-04
Filing Date
2026-02-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

进一步具体而言,一般而言,用于积层膜的绝缘树脂(或绝缘粘结树脂)以环氧系树脂为基础,混合固化剂、填充剂等制备而成,其中热膨胀系数越高,印刷电路板的翘曲(curl或warpage)不良发生越多,从而导致电路实现的匹配度降低;介电损耗越大,则微细电路设计越困难,因此需要具有低介电常数、低介电损耗、低热膨胀性及耐热性等特性

Benefits of technology

本发明的绝缘树脂及由其制备的积层膜(绝缘膜)在维持低介电常数、低介电损耗及低热膨胀系数的同时,不仅对铜镀层等导体,对绝缘体的附着力优异,并具有提升的伸长率特性。本发明的积层膜在使用时操作方便,并且由于FC-BGA(flip chip-ball greyarray)产品的生产性及使用时的耐冲击性得到提升,从而还可以提高可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935574A_ABST
    Figure CN122935574A_ABST
Patent Text Reader

Abstract

The present invention relates to an insulating resin and an insulating film or layer formed using the same, as a circuit material, which has a low thermal expansion coefficient and a low dielectric loss suitable for realizing a fine circuit, has excellent adhesion to a copper plating layer, and has excellent ductility, and is suitable for application as a build-up film of a printed circuit board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an insulating resin with improved ductility, which maintains the low coefficient of thermal expansion and low dielectric loss required for the realization of microcircuits, and to a multilayer film or insulating layer prepared therefrom, suitable for multilayer films for printed circuit boards. Background Technology

[0002] With the increasing functionality of electronic devices and the high integration of semiconductor devices, printed circuit boards (PCBs) are required to achieve high density, and multilayer PCBs have become the mainstream. As a manufacturing method for multilayer PCBs, the buildup method is well-known. The multilayer process is a method that involves etching a copper (Cu) multilayer board with copper-plated through-holes to form circuits, masking them with an insulating film, printing conductive ink onto the board to form the circuits, and then repeating the process of forming copper plating films on the conductive ink and through-holes to achieve multilayering.

[0003] Currently, multilayer printed circuit boards are manufactured using subtractive processes, modified semi-additive processes (MSAP), or semi-additive processes (SAP). The SAP process is used to manufacture the outer layers of the multilayer. The SAP process involves electrolytic copper plating and etching processes after copper plating to create the conductor circuit pattern.

[0004] The increasing integration and miniaturization of semiconductors used in electronic devices, communication equipment, personal computers, and other applications are accelerating. Consequently, the requirements for the properties of semiconductor packaging laminates (e.g., metal-clad laminates) used in printed circuit boards are becoming increasingly stringent. More specifically, the insulating resin (or insulating adhesive resin) used in the laminate is generally based on epoxy resin and prepared by mixing curing agents, fillers, etc. A higher coefficient of thermal expansion leads to more warpage defects on the printed circuit board, resulting in reduced circuit matching. Higher dielectric loss makes microcircuit design more difficult; therefore, properties such as low dielectric constant, low dielectric loss, low thermal expansion, and heat resistance are required.

[0005] To address this, the filler content in the insulating resin used in laminated films is increased as much as possible to impart a low coefficient of thermal expansion. However, a high filler content significantly reduces the elongation properties of the laminated film, leading to increased brittleness and problems such as reduced processability and increased defect rates, including cracks. Summary of the Invention

[0006] The technical problem that the invention aims to solve This invention relates to a method for manufacturing multilayer printed circuit boards by alternating layers of conductor circuit layers and insulating layers. The aim is to provide an optimal composition of insulating resin that improves ductility while maintaining a low coefficient of thermal expansion of the laminated film (thin film layer) as the insulating layer material, thereby improving operability and long-term product stability, as well as a laminated film (insulating layer) formed using the insulating resin.

[0007] means for solving problems To address the aforementioned issues, the present invention provides an insulating resin with improved ductility, comprising an epoxy blend resin, a modified epoxy resin, an adhesive resin, a curing agent, a curing accelerator, and a filler.

[0008] In a preferred embodiment of the present invention, the epoxy mixed resin may include two or more selected from biphenyl-based epoxy resins, bisphenol A-based epoxy resins, and naphthalene-based epoxy resins.

[0009] In a preferred embodiment of the present invention, the epoxy mixed resin may include naphthalene-based epoxy resin and biphenyl-based epoxy resin in a weight ratio of 1:0.3 to 0.8, or include naphthalene-based epoxy resin, biphenyl-based epoxy resin and bisphenol A-based epoxy resin in a weight ratio of 1:0.3 to 0.8:0.5 to 1.2.

[0010] In a preferred embodiment of the present invention, the modified epoxy resin may include one or more of the following: carboxyl-terminated butadiene acrylonitrile (CTBN) modified epoxy resin and nitrile-butadiene rubber (NBR) modified epoxy resin.

[0011] In a preferred embodiment of the present invention, the modified epoxy resin may be a modified epoxy resin modified from carboxyl-terminated butadiene acrylonitrile (CTBN) or nitrile rubber (NBR) with a modification rate of 13.0 to 22.0%.

[0012] In a preferred embodiment of the present invention, the adhesive resin may include one or more selected from phenoxy resin, polyvinyl butyral (PVB) resin, and nitrile rubber (NBR) resin.

[0013] In a preferred embodiment of the present invention, the curing agent may include one or more selected from phenolic curing agents, naphthalene-type curing agents, dicyclopentadiene (DCPD) norvolox type curing agents, and cresol norvolox type curing agents.

[0014] In a preferred embodiment of the present invention, the curing accelerator may include one or more of the following: imidazole-based curing accelerators, triallyl isocyanurate-based curing accelerators, and dicumyl peroxide-based curing accelerators.

[0015] In a preferred embodiment of the present invention, the imidazole-based curing accelerator may include one or more selected from 1-methylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole and 2-phenyl-4-methylimidazole.

[0016] In a preferred embodiment of the present invention, the triallyl isocyanurate-based curing accelerator may include one or more selected from triallyl isocyanurate, trivinylcyclohexane, and vinyl benzyl oxide.

[0017] In a preferred embodiment of the present invention, the dicumyl peroxide curing accelerator may include one or more selected from acetyl peroxide, benzoyl peroxide, and polyethylene.

[0018] In a preferred embodiment of the present invention, the filler may include one or more selected from silicon dioxide (SiO2) and silicon dioxide (SiO2) modified with silane compounds.

[0019] In a preferred embodiment of the present invention, the average particle size (D) of the filler 50 The size can range from 0.20 to 3.5 μm.

[0020] In a preferred embodiment of the present invention, the silane compound may include a compound represented by the following chemical formula 1.

[0021]

Chemical Formula 1

[0022] As a preferred embodiment of the present invention, the insulating resin for improving ductility of the present invention, based on solids, may include 8.0 to 20.0% by weight of epoxy mixed resin, 1.0 to 4.0% by weight of modified epoxy resin, 3.0 to 10.0% by weight of adhesive resin, 5.0 to 15.0% by weight of curing agent, 0.01 to 1.00% by weight of curing accelerator, and filler in the remainder of 100% by weight.

[0023] Another object of the present invention relates to a laminated film (or insulating film) comprising the insulating resin. As a preferred embodiment of the present invention, the coefficient of thermal expansion (CTE) of the laminated film of the present invention after curing at 30 to 150°C can satisfy the following equation 1.

[0024] Equation 1 20.00 ppm / ℃ ≤ CTE α1 ≤ 25.00 ppm / ℃ In Equation 1, the CTE α1 value is the coefficient of thermal expansion in the X and / or Y directions.

[0025] As a preferred embodiment of the present invention, the laminated film of the present invention, when measured according to the JIS K7113 method, can meet the requirement of an elongation of 5% or more.

[0026] In a preferred embodiment of the present invention, the laminated film of the present invention, after curing, has a dielectric constant (Dk) of less than 3.50 and a dielectric loss (Df) of 0.0010 to 0.0150 at 10 GHz when measured by the SPDR (splitpost dielectric resonators) method.

[0027] In a preferred embodiment of the present invention, the laminated film of the present invention, after curing, can meet the requirement of an adhesion of 0.40 kgf / cm or more when measuring the adhesion to the copper plating layer. Another object of the present invention is to provide a printed circuit board comprising an insulating layer or laminate (or insulating film) formed from a cured product of the aforementioned insulating resin. Furthermore, the present invention can also provide a method for using the aforementioned insulating resin when manufacturing multilayer printed circuit boards using a semi-additive patterning (SAP) process.

[0028] The effects of the invention The insulating resin and the laminated film (insulating film) prepared therefrom of the present invention maintain low dielectric constant, low dielectric loss, and low coefficient of thermal expansion, while exhibiting excellent adhesion not only to conductors such as copper plating but also to insulators, and improved elongation characteristics. The laminated film of the present invention is easy to handle during use, and its reliability is also improved due to the enhanced manufacturability and impact resistance of FC-BGA (flip chip-ball greyarray) products during use. Attached Figure Description

[0029] Figure 1 This is a schematic cross-sectional view of a multilayer printed circuit board with stacked insulating films or multilayer films according to the present invention. Detailed Implementation

[0030] In this specification, expressions such as "having", "may have", "includes" or "may include" refer to the presence of corresponding features (e.g., numerical values, functions, actions, or components) and do not exclude the presence of additional features.

[0031] It should be understood that all figures and expressions in this specification indicating the amount of constituent components, reaction conditions, etc., are modified with the term "about" in all cases, unless otherwise stated.

[0032] The present invention will now be described in more detail.

[0033] Insulating resins used to manufacture laminated films generally include epoxy resins and binder resins, and they should form a suitable chain structure through a reaction between them. However, while these components can be physically mixed, they cannot actually be chemically cross-linked. To solve this problem, the present invention introduces a modified epoxy resin that modifies the epoxy resin with binder components having a specific structure, inducing physical and chemical chain structures, thereby enabling the manufacture of insulating resins and laminated films (insulating films, insulating layers) made therefrom while maintaining a low coefficient of thermal expansion. The insulating resin of the present invention includes epoxy mixed resin, modified epoxy resin, adhesive resin, curing agent, curing accelerator and filler.

[0034] In the insulating resin composition of the present invention, the epoxy mixed resin may include two or more selected from biphenyl epoxy resin, bisphenol A epoxy resin and naphthalene epoxy resin. As a preferred example, if the insulating resin comprises two types of epoxy resin, they can be in a weight ratio of 1:0.3 to 0.8, preferably 1:0.40 to 0.70, and more preferably 1:0.40 to 0.60, comprising naphthalene-based epoxy resin and biphenyl-based epoxy resin. In this case, if the amount of biphenyl-based epoxy resin used is less than 0.3 by weight, there may be a decrease in the coefficient of thermal expansion; if it is used at a weight ratio exceeding 0.70, there may be an increase in brittleness. Furthermore, if the insulating resin comprises three epoxy resins, it can include naphthalene-based epoxy resin, biphenyl-based epoxy resin, and bisphenol A-based epoxy resin in a weight ratio of 1:0.3–0.8:0.5–1.2, preferably 1:0.42–0.78:0.55–1.1, and more preferably 1:0.44–0.75:0.55–1.1. In this case, if the amount of bisphenol A-based epoxy resin used is less than 0.5 by weight, it may not improve brittleness; if it exceeds 1.2 by weight, it may reduce the coefficient of thermal expansion and dielectric loss characteristics.

[0035] Furthermore, the naphthalene-based epoxy resin may use 1,6-bis(2,3-epoxypropoxy)naphthalene (CAS No. 27610-48-6), etc.

[0036] Furthermore, the biphenyl-based epoxy resin can be an epoxy resin having one or more biphenyl structural units in the epoxy resin. Furthermore, the biphenyl-based epoxy resin can be an epoxy resin that is solid or liquid at 25°C, preferably a liquid epoxy resin at 25°C. In addition, using a biphenyl-based epoxy resin with an epoxy equivalent of 250 g / eq to 300 g / eq is beneficial for achieving the effects of this invention.

[0037] Furthermore, the bisphenol A-based epoxy resin may include conventional bisphenol A-based epoxy resins known to those skilled in the art. Specifically, the bisphenol A-based epoxy resin may be an epoxy resin having one or more bisphenol A-based structural units. The bisphenol A-based epoxy resin may be an epoxy resin that is in a solid or liquid phase at 25°C, preferably an epoxy resin that is in a liquid phase at 25°C. Moreover, using an epoxy equivalent of 150 g / eq to 190 g / eq in the bisphenol A-based epoxy resin is beneficial for achieving the effects of the present invention.

[0038] Furthermore, in the total weight of the insulating resin of the present invention, the content of the epoxy mixed resin, based on solids, may include 8.0 to 20.0% by weight, preferably 10.0 to 18.0% by weight, and more preferably 10.0 to 17.0% by weight. If the content of the epoxy mixed resin is less than 8.0% by weight, there may be serious problems with insufficient adhesion and insulation; if it exceeds 15% by weight, there may be problems with reduced dielectric properties.

[0039] Next, in the insulating resin composition of the present invention, the modified epoxy resin plays a role in improving elongation characteristics. The modified component induces the bonding with the binder resin, thereby improving the overall energy level of the laminated film (insulating layer) and preventing phase separation between different components, thus improving the physical mixing properties. The modified epoxy resin includes one or more selected from carboxyl-terminated butadiene acrylonitrile (CTBN) modified epoxy resin and nitrile-butadiene rubber (NBR) modified epoxy resin. Preferably, a modified epoxy resin modified with carboxyl-terminated butadiene acrylonitrile (CTBN) or nitrile-butadiene rubber (NBR) at a modification rate of 13.0 to 22.0% is used. More preferably, a modified epoxy resin modified with CTBN or NBR at a modification rate of 15.0 to 20.0% is used. At this point, if the modification rate is less than 13.0%, the effect of improving ductility brought about by using modified epoxy resin may not be significant; if the modification rate exceeds 22.0%, there may be an increase in the coefficient of thermal expansion without any additional improvement in ductility. Furthermore, the modified epoxy resins of carboxyl-terminated butadiene acrylonitrile (CTBN) or nitrile rubber (NBR) include one or more selected from trimethylolpropane triglycidyl ether, diglycidyl ether (DGEBA, iglycidyl Ether of Bisphenol A), and diglycidyl ether (DGEBF, diglycidyl Ether of Bisphenol F), preferably including one or more selected from trimethylolpropane triglycidyl ether and DGEBA.

[0040] Furthermore, in the total weight of the insulating resin of the present invention, the content of the modified epoxy resin, based on solids, can be 1.0 to 4.0% by weight, preferably 1.0 to 3.6% by weight, and more preferably 1.0 to 3.4% by weight. In this case, if the content of the modified epoxy resin is less than 1.0% by weight, the amount used is too small, and the improvement in ductility may not be significant; if it exceeds 4% by weight, problems such as reduced dielectric properties and difficulty in maintaining a low coefficient of thermal expansion may occur.

[0041] Next, in the insulating resin composition of the present invention, the binder resin, as a component forming the skeleton of the insulating resin cured body (laminated film, insulating layer), may include one or more selected from phenoxy resin, polyvinyl butyral (PVB) resin and nitrile-butadiene rubber (NBR) resin, or may include two or more selected from phenoxy resin, PVB resin and NBR resin, and more preferably, the above three resins are mixed and used.

[0042] When the three resins are used in combination, based on 100 parts by weight of phenolic resin, it is appropriate to mix 50 to 150 parts by weight of polyvinyl butyral (PVB) resin and 50 to 150 parts by weight of nitrile rubber (NBR) resin.

[0043] Furthermore, in the total weight of the insulating resin of the present invention, the content of the binder resin, based on solids, can be 3.0 to 10.0% by weight, preferably 3.5 to 8.5% by weight, more preferably 4.0 to 8.0% by weight. If the content of the binder resin is less than 3.0% by weight, it may lead to poor coatability, morphological retention of the cured body, and mechanical properties; if it exceeds 10.0% by weight, it may cause problems with the performance of the main characteristics of the laminated film (e.g., coefficient of thermal expansion, dielectric loss, and mechanical properties).

[0044] Next, in the insulating resin composition, the curing agent provides adhesion and strength to the laminated film by forming crosslinking bonds with the epoxy resin. The curing agent may include one or more selected from phenolic curing agents, naphthalene-type curing agents, dicyclopentadiene (DCPD) norvolox type curing agents and cresol norvolox type curing agents, preferably including one or more selected from phenolic curing agents and DCPD norvolox type curing agents, and more preferably, the phenolic curing agent and DCPD norvolox type curing agent are mixed at a weight ratio of 1:0.05 to 0.20. Furthermore, in the insulating resin of the present invention, the content of the curing agent, based on solids, is 5.0 to 15.0% by weight, preferably 7.0 to 14.0% by weight, more preferably 8.0 to 14.0% by weight. If the curing agent content in the insulating resin is less than 5.0% by weight, the cured insulating resin may exhibit insufficient adhesion and poor mechanical properties; if it exceeds 15.0% by weight, compatibility and workability may decrease due to resin gelation. Therefore, it is preferable to use it within the above-mentioned range.

[0045] Next, in the composition of the insulating resin, the curing accelerator may include one or more selected from imidazole-based curing accelerators, triallyl isocyanurate-based curing accelerators, and dicumyl peroxide-based curing accelerators. Furthermore, the imidazole-based curing accelerator may include one or more selected from 1-methylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole.

[0046] In addition, the triallyl isocyanurate-based curing accelerator may include one or more selected from triallyl isocyanurate, trivinylcyclohexane, and vinyl benzyl oxide. In addition, the dicumyl peroxide-based curing accelerator may include one or more selected from acetyl peroxide, benzoyl peroxide, and polyethylene.

[0047] Furthermore, in the insulating resin of the present invention, the content of the curing accelerator, based on solids, is 0.01 to 1.00% by weight, preferably 0.02 to 0.50% by weight, and more preferably 0.02 to 0.30% by weight. When the content of the curing accelerator is less than 0.01% by weight, its dosage is too small, and the curing promotion effect may be insignificant; when it exceeds 1.00% by weight, there may be a problem of changes in the physical properties of the cured insulating resin over time. Therefore, it is preferable to control its content within the above-mentioned range.

[0048] In the composition of the insulating resin, the filler may be an inorganic filler such as silica, which is commonly used in the art. Furthermore, to enhance the dispersibility of the filler in the insulating resin, the formation of surface roughness after descaling, and the adhesion of the copper plating, the present invention may also use silica (SiO2) surface-modified with a silane compound as shown in Chemical Formula 1 below as a filler.

Chemical Formula 1

[0049] Furthermore, the average particle size (D) of the filler 50 The average particle size (D) can be 0.20–3.50 μm, preferably 0.50–3.50 μm. Within this range, the coefficient of thermal expansion of the insulating film can be reduced, and the dielectric properties can be improved. 50 The value was determined using the laser diffraction method.

[0050] Furthermore, the silica in the surface-modified silica is non-core-shell silica, which can be solid silica or hollow silica, and can be spherical, amorphous, etc., but spherical silica is preferred.

[0051] Furthermore, in the insulating resin of the present invention, the content of the filler is the balance after deducting epoxy mixed resin, modified epoxy resin, binder resin, curing agent and curing accelerator from the total weight % of the insulating resin.

[0052] Furthermore, when manufacturing films, insulating layers (coatings), etc., using the insulating resin of the present invention, a silane coupling agent may be further included to improve the peel strength of the insulating film. In this case, the silane coupling agent may include conventional silane coupling agents known to those skilled in the art, including alkoxysilanes such as amino-based, epoxy-based, (meth)acrylic-based, and mercapto-based alkoxysilanes, preferably ureoyl (C1-C5 alkyl)tri(C1-C5 alkoxy)silanes such as γ-ureapropyltrimethoxysilane. Moreover, when using a silane coupling agent, its content, based on solids percentage, is preferably 0.01 to 1.00% by weight of the total weight of the insulating resin. Using it within this range avoids the problem of uneven thickness on the surface of the insulating film, and when used as an adhesive composition for insulating films, it also avoids changes in the basic physical properties of the adhesive and the problem of chemical solution contamination during chemical copper plating.

[0053] Furthermore, the insulating resin of the present invention may further include BT (bismaleimide triazine) resin, surfactants, dispersants, and other additives.

[0054] In the above-mentioned additives, the BT resin is used to improve the heat resistance of the insulating film, and a non-reactive cyanate ester can be used. The BT resin can be a commercially available product or prepared by methods known to those skilled in the art. Furthermore, when using the BT resin, its content, based on solids percentage, is preferably 1.0 to 10.0% by weight of the total weight of the insulating resin. When used within this range, an appropriate improvement in the heat resistance of the insulating film can be obtained without causing brittleness in the insulating film.

[0055] In the aforementioned additives, the surfactant is used to improve film-forming properties when the insulating resin is formed into a film or coating layer. Commonly known to those skilled in the art, such as sodium dodecyl benzene sulfonate (SDBS), polyoxyethylene nonylphenyl ether, Pluronic F127, etc., can be selected. Furthermore, when using the surfactant, its content, based on solids percentage, is 0.01 to 1.00% by weight of the total weight of the insulating resin; use within this range is suitable for improving the film-forming properties of the insulating film. The dispersant, included in the adhesive composition for insulating films, prevents silica aggregation and improves silica dispersibility, thereby maintaining a stable coefficient of thermal expansion of the insulating film. When using the dispersant, its content, based on the solid content, is 0.1 to 2.0% by weight of the total weight of the insulating resin. Using it within this range avoids the problem of filler aggregation and does not cause changes in the basic properties of the insulating resin.

[0056] The above-mentioned insulating resin is coated on one side of the carrier film and then dried to form a laminated film, an insulating film, or an insulating layer.

[0057] Furthermore, although there is no particular limitation on the thickness of the laminated film, insulating film, or insulating layer, it can be 25μm to 50μm when considering its application on printed circuit boards.

[0058] After curing, the coefficient of thermal expansion (CTE) of the laminated film, insulating film or insulating layer of the present invention at 30 to 150°C can satisfy the following equation 1.

[0059] Equation 1 20.00 ppm / ℃ ≤ CTE α1 ≤ 25.00 ppm / ℃, preferably 21.00 ppm / ℃ ≤ CTE α1 ≤ 25.00 ppm / ℃ In Equation 1, the CTE α1 value is the coefficient of thermal expansion in the X-axis and / or Y-axis directions.

[0060] Furthermore, when the laminated film, insulating film, or insulating layer is measured according to JIS K7113, its elongation can meet the requirement of 5% or more, preferably 5.0 to 8.0%.

[0061] After curing, the laminated film, insulating film, or insulating layer of the present invention, when measured according to the SPDR (split postdielectric resonators) method, has a dielectric constant (Dk) at 10 GHz. k The dielectric loss (D) can be below 5.50. f The dielectric constant (D) can be 0.0010 to 0.0150; preferably at 10 GHz, its dielectric constant (D) is... k The dielectric loss (D) is below 3.40. f The range is 0.0010 to 0.0130.

[0062] When the adhesion of the multilayer film, insulating film, or insulating layer described in this invention to a copper plating layer is measured, the adhesion can be 0.40 kgf / cm or higher, preferably 0.40 to 0.80 kgf / cm, and more preferably 0.40 to 0.65 kgf / cm. This high adhesion can provide stable adhesion stability for the substrate and circuit.

[0063] The present invention provides a printed circuit board comprising a multilayer film, an insulating film, or an insulating layer formed from a cured product of the aforementioned insulating resin.

[0064] In addition, a method for using the above-mentioned insulating resin when manufacturing multilayer printed circuit boards using the semi-additive patterning (SAP) process can also be provided.

[0065] The insulating film or the multilayer film can be used in the manufacture of multilayer printed circuit boards.

[0066] Figure 1 A printed circuit board with insulating films (110a, 110b) stacked according to an embodiment of the present invention is shown. Figure 1 As shown, the insulating film 110a is in contact with the stacked insulating film 110b, the substrate 200, the first circuit 210 and the second circuit 220.

[0067] Multilayer printed circuit boards can be manufactured using conventional methods known to those skilled in the art. In one specific embodiment, an adhesive composition for insulating film is coated to a specified thickness on one side of a carrier film, and then dried at a temperature of 80°C to 110°C for 1 to 10 minutes to form an insulating film. A cover film is then attached to one side of the insulating film, thereby manufacturing a laminated film (or insulating sheet) consisting of a cover film, an insulating film, and a carrier film.

[0068] An insulating film is obtained by peeling off a cover film from a laminated film. This insulating film is then vacuum-bonded onto a substrate or similar material using a vacuum laminator, followed by pre-baking. The pre-baking can be performed at a predetermined temperature (e.g., 100°C to 170°C) and for a predetermined time (e.g., 60 minutes to 120 minutes). Subsequently, an electroplating process is applied to the surface of the pre-baked insulating film, allowing it to fully cure. Full curing of the insulating film can be performed at 150°C to 200°C for 60 to 120 minutes, but is not limited to this. Furthermore, a desmearing process can be performed before the electroplating process.

[0069] The method for manufacturing a printed circuit board according to the present invention includes the step of using an insulating film formed from the insulating resin of the present invention. The method for manufacturing a printed circuit board according to the present invention may involve using an insulating film formed from the insulating film adhesive composition of the present invention during the manufacture of a general circuit wiring board. Hereinafter, each step of the method for manufacturing a printed circuit board according to the present invention will be described in detail, but the present invention is not limited thereto.

[0070] The method for manufacturing a printed circuit board includes the following steps: (A) coating a support with the thermosetting insulating resin of the present invention to form an insulating film coating of a predetermined thickness; (B) bonding the support and the insulating film coating to a circuit board, thereby bonding the insulating film coating to the circuit board; (C) curing the insulating film coating to form an insulating film; (D) perforating the insulating film to form via holes; (E) performing desmear treatment; and (F) forming a conductor layer on the surface of the insulating layer.

[0071] Process (A) Process (A) involves applying a thermosetting insulating resin to the support at a predetermined thickness to form an insulating film.

[0072] The support can be a film made of plastic material, metal foil (copper foil or aluminum foil), or release paper, etc. The support can also have a structure in which a release layer is further laminated on the surface that is bonded to the insulating resin.

[0073] The thermosetting insulating resin used in this invention, after being coated onto a support at a predetermined thickness, can be used to form an insulating film by solvent drying or the like.

[0074] Process (B) Process (B) involves bonding the support and the insulating film coating to the circuit board, thereby bonding the insulating film coating to the circuit board.

[0075] The insulating film coating can also be pretreated before bonding to the circuit board. The pretreatment method can be CZ pretreatment, which is an etching process.

[0076] The bonding can generally be achieved by appropriately adjusting the pressing pressure, pressing temperature and pressing time, and by using a vacuum laminator.

[0077] Process (C) Step (C) involves curing the coating for the insulating film to form an insulating film. Specifically, this is done by heat curing the coating for the insulating film to form an insulating layer. The heat curing conditions are not particularly limited, and conditions typically used when forming insulating layers for circuit boards can be used. The heat curing can be performed at 150°C to 200°C for 60 to 120 minutes, but is not limited to these conditions.

[0078] Before heat curing the coating for insulating film, pre-curing can be performed at a temperature lower than the heat curing temperature. For example, before heat curing the coating for insulating film, pre-curing can be performed at 30°C to 40°C for 10 to 30 minutes.

[0079] Process (D) Process (D) involves perforating the insulating film to form via holes. These vias are formed to enable interlayer electrical connections and, considering the properties of the insulating layer, can be formed using known methods such as drilling, lasers, and plasma. The laser source can be a carbon dioxide laser, a YAG laser, an excimer laser, etc.

[0080] Process (E) Process (E) involves desmearing. Resin residue adheres to the interior of the through-holes formed in process (D), and this residue can cause poor interlayer electrical connections, therefore it needs to be removed. Desmearing can be performed using conventional methods, including dry desmearing, wet desmearing, or a combination thereof. Dry desmearing can utilize plasma. Wet desmearing can utilize oxidant solutions, etc.

[0081] Process (F) Process (F) includes the process of forming a conductor layer on the surface of the insulating layer.

[0082] The conductor layer can be formed using a semi-additive process (SAP). A seed layer is formed on the surface of the insulating layer by chemical plating, and a mask pattern is formed to expose a portion of the seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed seed layer by electrolytic plating, the mask pattern is removed, and unnecessary seed layers are removed by etching, thereby forming a conductor layer with the desired wiring pattern.

[0083] The present invention will be described in more detail below through embodiments, but the following embodiments do not limit the scope of the present invention and should be interpreted as helping to understand the present invention.

[0084]

Example

[0085] (A) Epoxy-based mixed resin (A1) Bisphenol A-based epoxy resin (trade name: YD-128, Guodu Chemical, epoxy equivalent 150g / eq~190g / eq) (A2) Biphenyl-based epoxy resin (trade name: NC-3000, Nippon Kayaku, epoxy equivalent 250-300 g / eq) (A3) Naphthalene-based epoxy resin (trade name: SE-80, Xinya T&C, CAS No.27610-48-6) (B) Modified epoxy resin (B1) Carboxyl-terminated butadiene acrylonitrile (CTBN) modified epoxy resin This is an epoxy resin obtained by modifying trimethylolpropane triglycidyl ether (CAS No. 30499-70-8) with carboxyl-terminated butadiene acrylonitrile (CTBN) at 15%, 20%, or 30%.

[0086] (B2) Acrylonitrile rubber (NBR) modified epoxy resin This is an epoxy resin obtained by modifying epoxy resin DGEBA (Diglycidyl Ether of Bisphenol A) with nitrile rubber (NBR) at 20%.

[0087] (B3) Acrylic modified epoxy resin (trade name: PARACRON EG26R, manufacturer: Negami, Japan) (B4) Rubber-modified epoxy resin (trade name: UME-305, manufacturer: Guodu Chemical), wherein the rubber is polyurethane rubber.

[0088] (C) Adhesive resin (C1) Phenoxy resin (trade name: HE-1900, manufacturer: HE Chem) (C2) Polyvinyl butyral (PVB) resin (trade name: BM-SZ, manufacturer: Sekisui) (C3) Nitrile butadiene rubber (NBR) resin (trade name: CBE-101, manufacturer: CHEMBASE) (D) Curing agent (D-1) Phenolic curing agent (trade name: SCP-110, manufacturer: Xinya T&C) (D-2) Dicyclopentadiene (DCPD) Novolok type curing agent (trade name: KDN-7280, manufacturer: Guodu Chemical) (E) Curing accelerator (E1) Imidazole-based curing accelerator 1 uses 2-ethyl-4-methylimidazole (2-ethyl-4-methylimidazole, trade name: 2E4MZ, manufacturer: Shikoku Kasei Kogyo).

[0089] (E2) Imidazole-based curing accelerator 2 uses 1-benzyl-2-phenylimidazolium (1-benzyl-2-phenylimidazolium, trade name: 1B2PZ, manufacturer: Shikoku Kasei Kogyo).

[0090] Example 1: Manufacturing of insulating resin A mixture of naphthalene-based epoxy resin and biphenyl-based epoxy resin was prepared by mixing, stirring and heating to dissolve CTBN-modified epoxy resin (modification rate 15%).

[0091] Furthermore, after mixing the binder resin, curing agent, curing accelerator, and filler in the mixture, the mixture is uniformly dispersed using a mixer to prepare an insulating resin, and the content of each component is shown in Table 1 below. Here, the content is expressed as solids.

[0092] The adhesive resin used is phenoxy resin, polyvinyl butyral (PVB) resin, and nitrile rubber (NBR) resin.

[0093] In addition, phenolic curing agents and DCPD Novolok type curing agents are used as curing agents. In addition, imidazole-based curing accelerator 2 is used as a curing accelerator. In addition, silica (average particle size D) is used as a filler. 50 =0.5μm). Examples 2-11 and Comparative Examples 1-11 Insulating resins were prepared using the same composition as in Example 1 above, but the content of each component was changed as shown in Tables 1 to 3 below. Examples 1 to 11 and Comparative Examples 1 to 11 were then carried out respectively.

[0094] Experimental Example 1: Physical Property Measurement Insulating films were manufactured using the insulating resins prepared in the Examples and Comparative Examples, and the physical properties shown in Tables 1 to 3 below were evaluated. During the physical property testing, the curing was performed as a thermosetting process, which involved thermosetting the insulating film at 190°C for 60 minutes.

[0095] (1) Coefficient of thermal expansion (unit: ppm / ℃): After the insulating film is cured, the coefficient of thermal expansion is measured using a TMA device at a heating rate of 10℃ from 25℃ to 260℃. The coefficient of thermal expansion in the X-axis and Y-axis directions is evaluated and expressed as the coefficient of thermal expansion value in the range of 30 to 150℃.

[0096] (2) Dielectric properties (Dk): After the insulating film is cured, the dielectric constant (Dk) and dielectric loss (Df) at a frequency of 10 GHz are measured using a dielectric property measuring device.

[0097] (3) Adhesion (kgf / cm): After the insulating film is cured, an electrolytic copper plating layer with a thickness of 20μm is applied to the cured insulating film. Then, the adhesion between the cured insulating film and the copper plating layer is measured using an adhesion measuring device under the conditions of peeling temperature of 25℃, peeling angle of 90° and peeling speed of 50mm / min. (4) Elongation (%): The elongation is measured using UTM equipment according to the JIS K7113 method, and an elongation of 5% or more is considered qualified.

[0098] Table 1

[0099] Table 2

[0100] Table 3

[0101] Observing the physical property test results in Tables 1 to 3 above, it can be confirmed that the insulating resins of Examples 1 to 11 have a low dielectric constant (Dk) of less than 3.50 and a low dielectric loss (Df) of less than 0.0150, as well as an appropriate coefficient of thermal expansion (20.00 to 25.00 ppm / ℃), a high elongation of more than 5%, and high adhesion.

[0102] In contrast, Comparative Example 1 and Comparative Example 7, which did not use modified epoxy resin, had problems with excessively low elongation, and Comparative Example 7 also had a coefficient of thermal expansion exceeding 25 ppm / ℃. Furthermore, in Comparative Example 2, where the amount of modified epoxy resin used exceeded 4% by weight, there was a problem of excessively high coefficient of thermal expansion.

[0103] Furthermore, in Comparative Example 3, which used NBR-modified epoxy resin instead of CTBN-modified epoxy resin, there was a problem of lower elongation.

[0104] Furthermore, in Comparative Example 4, where the amount of epoxy mixed resin used exceeded 20% by weight, the coefficient of thermal expansion increased due to the relatively reduced content of filler.

[0105] Furthermore, in Comparative Examples 5 and 6, which used 30% modified epoxy resin with a modification rate of more than 22% as CTBN modified epoxy resin, there was a problem that the coefficient of thermal expansion was too high, exceeding 25.00 ppm / ℃.

[0106] Furthermore, in Comparative Examples 8 and 9, which used acrylic-modified epoxy resin instead of CTBN-modified epoxy resin, there were problems with low elongation and excessively high coefficient of thermal expansion. In Comparative Examples 10 and 11, which used rubber-modified epoxy resin, there were problems with high coefficient of thermal expansion and dielectric loss exceeding 0.0150.

[0107] The insulating resin and the insulating film prepared therefrom of the present invention have low dielectric constant, low dielectric loss and low coefficient of thermal expansion, and have excellent adhesion not only to conductors such as copper plating, but also to insulators, and the elongation can be confirmed to reach more than 5%. Furthermore, the insulating film prepared from the insulating resin of the present invention has a low surface roughness and a uniform surface, so as a build-up film, especially when applied to the semi-additive process (SAP), it can maintain a uniform surface roughness even after plasma treatment and / or desmearing processes used to manufacture multilayer printed circuit boards.

Claims

1. An insulating resin with improved ductility, characterized in that, include: Epoxy blends, modified epoxy resins, adhesive resins, curing agents, curing accelerators, and fillers. The epoxy mixed resin includes two or more selected from biphenyl-based epoxy resins, bisphenol A-based epoxy resins, and naphthalene-based epoxy resins. The modified epoxy resin includes one or more selected from carboxyl-terminated butadiene acrylonitrile (CTBN) modified epoxy resin and nitrile rubber (NBR) modified epoxy resin.

2. The insulating resin with improved ductility according to claim 1, characterized in that, The epoxy mixed resin comprises naphthalene-based epoxy resin and biphenyl-based epoxy resin in a weight ratio of 1:0.3 to 0.8, or It includes naphthalene-based epoxy resins, biphenyl-based epoxy resins, and bisphenol A-based epoxy resins in a weight ratio of 1:0.3 to 0.8:0.5 to 1.

2.

3. The insulating resin with improved ductility according to claim 1, characterized in that, The modified epoxy resin is a modified epoxy resin modified from carboxyl-terminated butadiene acrylonitrile (CTBN) or nitrile rubber (NBR) with a modification rate of 13.0% to 22.0%.

4. The insulating resin with improved ductility according to claim 1, characterized in that, The adhesive resin includes one or more selected from phenoxy resin, polyvinyl butyral (PVB) resin, and nitrile rubber (NBR) resin.

5. The insulating resin with improved ductility according to claim 1, characterized in that, The curing agent includes one or more selected from phenolic curing agents, naphthalene-type curing agents, dicyclopentadiene (DCPD) norvolox type curing agents, and cresol norvolox type curing agents; The curing accelerator includes one or more selected from imidazole-based curing accelerators, triallyl isocyanurate-based curing accelerators, and dicumyl peroxide-based curing accelerators. The imidazole-based curing accelerator includes one or more selected from 1-methylimidazolium, 2-methylimidazolium, 2-ethyl-4-methylimidazolium, 2-phenylimidazolium, and 2-phenyl-4-methylimidazolium; The triallyl isocyanurate-based curing accelerator includes one or more selected from triallyl isocyanurate, trivinylcyclohexane, and vinyl benzyl oxide; The dicumyl peroxide-based curing accelerator includes one or more selected from acetyl peroxide, benzoyl peroxide, and polyethylene.

6. The insulating resin with improved ductility according to claim 1, characterized in that, The filler includes one or more selected from silicon dioxide (SiO2) and silicon dioxide (SiO2) surface-modified with silane compounds. The silane compounds include those represented by the following chemical formula 1; 【Chemical Formula 1】 R 3 NHR 2 Si(OR 1 )3 In chemical formula 1, R 1 It is hydrogen or a C1-C5 straight-chain alkyl group, a C3-C5 branched alkyl group, or a C1-C5 straight-chain alkoxy group. R 2 It is an alkylene group with 1 to 5 carbon atoms. R 3 It is a hydrogen atom, a C1-C3 straight-chain alkyl group, a C3-C5 branched alkyl group, a C3-C5 branched alkyl group, or a phenyl group with or without substituents.

7. The insulating resin with improved ductility according to claim 1, characterized in that, The average particle size (D) of the filler 50 The micrometer diameter (μm) ranges from 0.20 to 3.5 μm.

8. The insulating resin with improved ductility according to claim 1, characterized in that, Based on solids, it includes 8.0 to 20.0% by weight of epoxy blended resin, 1.0 to 4.0% by weight of modified epoxy resin, 3.0 to 10.0% by weight of adhesive resin, 5.0 to 15.0% by weight of curing agent, 0.01 to 1.00% by weight of curing accelerator, and the balance being 100% by weight of filler.

9. A laminated film, characterized in that, include: The insulating resin according to any one of claims 1 to 8.

10. The laminated film according to claim 9, characterized in that, After curing, the coefficient of thermal expansion (CTE) of the laminated film at 30–150°C satisfies the following equation 1; Equation 1 20.00ppm / ℃≤CTE α1≤25.00ppm / ℃ In Equation 1, the CTE α1 value is the coefficient of thermal expansion in the X and Y directions.

11. The laminated film according to claim 9, characterized in that, When measured according to JIS K7113 method, the elongation is 5% or more.

12. The laminated film according to claim 9, characterized in that, After curing, the laminated film, when measured by the split column dielectric resonator (SPDR) method, has a dielectric constant (Dk) of less than 3.50 and a dielectric loss (Df) of 0.0010 to 0.0150 at 10 GHz.

13. The laminated film according to claim 9, characterized in that, After curing, the adhesion of the laminated film to the copper plating layer is measured to be above 0.40 kgf / cm.

14. A printed circuit board, comprising: An insulating layer formed from a cured product of an insulating resin selected from any one of claims 1 to 8.